PERBEDAAN HASIL BELAJAR SISWA DITINJAU DARI MODEL SAVI DENGAN MODEL RECIPROCAL TEACHING - Nurfitriana Gayanti; Dewi Anggreini (STKIP PGRI Tulungagung, 2019)
This study aims to know about differences in student learning outcomes that are reviewed from the SAVI learning modelwith Reciprocal Teaching learning model on circle material. This quantitative quasi-experiment research carried in SMPN 1 Karangrejo with 348 population and sample takencluster random samplingso that there are 2 classes namely VIII D class as a SAVI learning model class with 32 students, and VIII B clas as a reciprocal teaching learning model class with 32 students. The data analize using t-test. After making a calculation with a significant level is 5% and dk 62 so obtained tcount= 7,141765 ttable= 1,99897, its mean H0 rejected and H1 received, so it was concluded that there was a significant difference between the learning outcomes of mathematics using the SAVI learning model and the Reciprocal Teaching learning model at the learning outcomes of mathematics on circle material at the students VIII class in SMPN 1 Karangrejo in the period 2017/2018Â Keywords:mathematics learning outcomes, SAVI, reciprocal teachin